Adopting the 5P Framework to Enhance Revitalization Policy Lessons from Cihampelas Terrace as a Public Space - Irawati, Ira; Ashari, David; Sandriano, Yoh.; Mareta, Ristia; Evangelistha, Sherin; Firmansyah, Angga; Rizal, Saiful (Universitas Padjadjaran, 2025)
This research aims to conduct a retrospective (ex post) policy analysis using a formative evaluation approach. This study identifies implementation challenges in the Cihampelas Terrace revitalization policy and evaluates its effectiveness. Using the 5P framework (principles, places, people, processes, and practices), the study examined issues such as inconvenient location, poor accessibility for people with disabilities and the elderly, and a 60% decrease in street vendors' turnover after relocation. A mixed methods approach with an explanatory sequential design was used. Data were collected through questionnaires distributed to visitors and street vendors and in-depth interviews with stakeholders. Findings showed a significant gap between policy objectives and implementation. Only 32% of respondents felt involved in the process, while 51% reported a lack of participation mechanisms. In addition, 42% rated the public facilities as inadequate, citing non-functioning elevators and poor hygiene. To address these issues, the study recommends an Integrated Collaborative Policy Framework, which combines hybrid public consultation, digital transparency platforms, and universal design principles. By utilizing data-driven analysis and interactive risk dashboards, the framework aims to improve community engagement, policy adaptation, and operational responsiveness, and ensure sustainable and inclusive public spaces like the Cihampelas Terrace.